Brazil's simplified tax regime and the longevity of Brazilian manufacturing companies: A survival analysis based on RAIS microdata - Otavio Canozzi Conceiç\~ao; Maurício Vitorino Saraiva; Adelar Fochezatto; Marco Túlio Aniceto França (EconomiA, 2018)
The article aims to analyze the effects of the Brazilian Simplified Tax Regime (Simples Nacional) on the longevity of manufacturing microenterprises, contributing to the current debate on the expansion of the program. Based on the RAIS (Relaç\~ao Anual de Informaç\~oes Sociais) microdata comprising the period between 2007-2013, a sample of manufacturing establishments, homogeneous in their economic structure, was selected and divided into two groups - those who opted for the program and those who did not. The Survival Analysis technique and the Propensity Score Matching made it possible to identify that the establishments opting for Simples Nacional that were created in 2007 had a 30% lower chance of mortality than the companies not opting for it. Another main result was the indication that separating manufacturing establishments by level of technology-intensiveness the Simplified Regime had a differentiated impact among the groups, with only the manufacturing establishments of low and medium-low technology-intensiveness sectors being affected.
Keywords: L20; C23; K34; 330; Brazilian Simplified Tax Regime; Industry; Propensity Score Matching; Survival Analysis; Tax policy